2019
DOI: 10.1208/s12249-019-1541-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Films to Anticipate Effect of Drug Load and Polymer on Dissolution Performance from Tablets of Amorphous Itraconazole Spray-Dried Dispersions

Abstract: Because spray-dried dispersion (SDD) performance depends on polymer selection and drug load, time-and resource-sparing methods to screen drug/polymer combinations before spray drying are desirable. The primary objective was to assess the utility of films to anticipate the effects of drug load and polymer grade on dissolution performance of tablets containing SDDs of itraconazole (ITZ). A secondary objective was to characterize the solid-state attributes of films and SDDs to explain drug load and polymer effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Hanada et al demonstrated atomic level drug-polymer interaction in ASD of Posaconazole and HPMC using 19 F solid-state NMR . Apart from this, there are multiple reports of drug-polymer miscibility using solid-state NMR. , …”
Section: Methods For the Evaluation Of Drug-polymer Solubility And Mi...mentioning
confidence: 99%
“…Hanada et al demonstrated atomic level drug-polymer interaction in ASD of Posaconazole and HPMC using 19 F solid-state NMR . Apart from this, there are multiple reports of drug-polymer miscibility using solid-state NMR. , …”
Section: Methods For the Evaluation Of Drug-polymer Solubility And Mi...mentioning
confidence: 99%
“…It is poorly water‐soluble and classified as BCS class II [3]. The drug is often used as a model drug for preparing amorphous solid dispersions either by spray drying or hot melt extrusion method for solubility enhancement [4–6]. Being a water‐insoluble molecule, there are also obvious challenges in developing a robust analytical method for the estimation of itraconazole from the formulation.…”
Section: Introductionmentioning
confidence: 99%